2021
DOI: 10.1093/eurheartj/ehab782
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect effects of the COVID-19 pandemic on cardiovascular disease throughout the world

Abstract: Graphical Abstract Graphical Abstract The direct and indirect impact of COVID-19 on cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…21,22 There were remarkable reductions in STEMI activations worldwide with substantial decrease in use of coronary angiography and PCI, longer door-toballoon and total ischemic times, and increased risk of mechanical complications. [21][22][23][24][25][26] In parallel, we observed a remarkable increase in In parallel with previous observations, 10,11 we found that late presenters were more likely to be older, female, and have a high cardiovascular risk profile. It is likely that atypical ischemic symptoms, known to be common in these patients, may delay seeking care.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…21,22 There were remarkable reductions in STEMI activations worldwide with substantial decrease in use of coronary angiography and PCI, longer door-toballoon and total ischemic times, and increased risk of mechanical complications. [21][22][23][24][25][26] In parallel, we observed a remarkable increase in In parallel with previous observations, 10,11 we found that late presenters were more likely to be older, female, and have a high cardiovascular risk profile. It is likely that atypical ischemic symptoms, known to be common in these patients, may delay seeking care.…”
Section: Methodssupporting
confidence: 87%
“…National and local actions to mitigate the pandemic, such as lockdown restrictions, social isolation with substantial fear of infection, and deferral of routine health care, subsequently resulted in unintended consequences in STEMI care 21,22 . There were remarkable reductions in STEMI activations worldwide with substantial decrease in use of coronary angiography and PCI, longer door‐to‐balloon and total ischemic times, and increased risk of mechanical complications 21–26 . In parallel, we observed a remarkable increase in late presenters (almost doubled) during the early phase of the Covid‐19 pandemic in 2020.…”
Section: Discussionmentioning
confidence: 74%
“…Conceptually, the COVID-19 pandemic has had direct (increased arterial and venous thrombogenicity, troponin elevation, microthrombi, respiratory failure, in-hospital presentation) and indirect effects (lockdowns, cancellation of services, restrictive visitation policies, delayed presentations) on acute MI care, which collectively have resulted in increased morbidity and mortality. 44 , 45…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, the COVID-19 pandemic has had direct (increased arterial and venous thrombogenicity, troponin elevation, microthrombi, respiratory failure, in-hospital presentation) and indirect effects (lockdowns, cancellation of services, restrictive visitation policies, delayed presentations) on acute MI are, which collectively have resulted in increased morbidity and mortality. 44 …”
Section: Introductionmentioning
confidence: 99%
“…It is clear that restrictive lockdowns are detrimental for healthcare delivery and more circumspect approaches are needed. 44 For effective results, such campaigns should be able to cross cultural, socioeconomic, and psychosocial barriers. Strategies for emergency network reorganization, including rapid screening of acute MI patients and appropriate allocation of resources for critically ill non-COVID patients, are also needed.…”
Section: Introductionmentioning
confidence: 99%